Simultaneous activity and stability increase of co-precipitated Ni–Al CO2 methanation catalysts by synergistic effects of Fe and Mn promoters. Issue 22 (26th October 2018) - Burger, Thomas; Koschany, Franz; Wenng, Andreas; Thomys, Oliver; Köhler, Klaus; Hinrichsen, Olaf
Abstract : The activity and stability of co-precipitated NiAlO x catalysts in the CO2 methanation reaction is targetedly enhanced by co-doping Fe and Mn. Abstract : For CO2 methanation, the development of highly active and thermostable catalysts is indispensable to cope with the demands of SNG purity in single-pass fixed-bed operation and the exothermal character of the reaction. In this work, a co-precipitated NiAlO x catalyst with an equimolar Ni/Al ratio is modified by the two promoters Mn and Fe. The combination of both dopants can be used to synthesize highly thermostable catalysts with an enhanced catalytic activity. The activity–stability performance is strongly dependent on the Ni/promoter ratios, with Ni/Mn = 9.5 and Ni/Fe = 7 performing best. Besides doping already during co-precipitation, it is shown that for doping via impregnation the activity–stability performance for a constant Ni/Fe/Mn ratio can be influenced by the preparation procedure. This offers the unique opportunity to target the activity–stability behavior of a co-precipitated NiAlO x catalyst as required.